Frontline Science: Conversion of neutrophils into atypical Ly6G+SiglecF+ immune cells with neurosupportive potential in olfactory neuroepithelium. Issue 3 (29th July 2020) - Ogawa, Kei; Asano, Kenichi; Yotsumoto, Satoshi; Yamane, Tsuyoshi; Arita, Makoto; Hayashi, Yoshihiro; Harada, Hironori; Makino‐Okamura, Chieko; Fukuyama, Hidehiro; Kondo, Kenji; Yamasoba, Tatsuya; Tanaka, Masato
Abstract: Neutrophils are generally considered as short‐lived, homogenous, and terminally differentiated phagocytes that play crucial roles in conquering infection, although they occasionally cause severe collateral tissue damage or chronic inflammation. Recent reports have indicated that neutrophils also play a protective role in inflammation resolution and tissue repair. However, how terminally differentiated neutrophils have diverse functions remains unclear. Here, we show that neutrophils undergo conversion into Ly6G + SiglecF + double‐positive cells expressing neurosupportive genes in the olfactory neuroepithelium (OE) under an inflammatory state. Through comprehensive flow cytometric analysis of murine nose, we identified Ly6G + SiglecF + double‐positive cells that reside only in the OE under steady‐state conditions. Double‐positive cells were neutrophil‐derived cells and increased by more than 10‐fold during inflammation or tissue injury. We found that neutrophils infiltrate into the nose to express proinflammatory genes in the acute phase of inflammatory state, and they gradually change their surface markers and gene expression, expressing some neurogenesis‐related genes in addition to inflammation related genes in the later phase. As the OE is known to have exceptionally high regeneration capacity as a nervous system, these findings suggest that neutrophils have the potential to contribute neurogenesis after conversion in peripheral nervous tissues, providing a challenge on a classic view of neutrophils as terminally differentiated leukocytes. Graphical Abstract: Neutrophils convert into Ly6G+SiglecF+ double‐positive cells expressing neurogenesis‐related genes in the olfactory neuroepithelium.